2010
DOI: 10.1016/j.commatsci.2010.06.009
|View full text |Cite
|
Sign up to set email alerts
|

FFT-based methods for the mechanics of composites: A general variational framework

Abstract: International audienceFor more than a decade, numerical methods for periodic elasticity, based on the fast Fourier transform, have been used successfully as alternatives to more conventional (fem, bem) numerical techniques for composites. These methods are based on the direct, point-wise, discretization of the Lippmann-Schwinger equation, and a subsequent truncation of underlying Fourier series required for the use of the fast Fourier transform. The basic FFT scheme is very attractive, because of its simplicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
284
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(289 citation statements)
references
References 23 publications
4
284
1
Order By: Relevance
“…They are referred to with a 'tilde' notation as DS, AS, AL, VAR, DS D , and AL D . We emphasize that the results presented here for the variational approaches VAR and VAR make use of the Green operators G 0 and G 0 rather than of the more complex discretization proposed in [14]. Also, in the latter approaches, definite-positiveness of matrix M (see Sec.…”
Section: Classical and Modified Green Operatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…They are referred to with a 'tilde' notation as DS, AS, AL, VAR, DS D , and AL D . We emphasize that the results presented here for the variational approaches VAR and VAR make use of the Green operators G 0 and G 0 rather than of the more complex discretization proposed in [14]. Also, in the latter approaches, definite-positiveness of matrix M (see Sec.…”
Section: Classical and Modified Green Operatorsmentioning
confidence: 99%
“…The alternative 'variational' algorithm [14] relies on two distinct ideas. First, Equation (3) is written as:…”
Section: Fft Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Monchiet and Bonnet [340] proposed a polarization-based FFT iterative scheme to determine the overall properties of multiphase composites with arbitrary phase contrast, see also Refs. [341][342][343][344]. The use of a discrete element formulation to resolve the RVE problem has been addressed in Refs.…”
Section: Analysis At the Rve Levelmentioning
confidence: 99%
“…First-order finite difference-based approximations composed onto Fourier transforms have been shown to result in significantly mitigating oscillatory artifacts (Müller, 1996;Brown et al, 2002;Berbenni et al, 2014;Brisard and Dormieux, 2010;Lebensohn and Needleman, 2016;Schneider et al, 2016), while maintaining consistency with the original governing equations with h-refinement. Willot et al (2014) showed that rotated first-order schemes show a marked reduction in oscillatory artifacts.…”
Section: Introductionmentioning
confidence: 99%